RANCANG BANGUN APLIKASI AL-QUR’AN MOBILE BERBASIS FLUTTER DENGAN FITUR MULTI MARKAH BACAAN DAN CATATAN - Muhammad Sutan Fathir; Jajam Haerul Jaman; Garno Garno (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
The rapid development of mobile technology has encouraged the emergence of various digital Qur'an applications that facilitate users in reading the Qur'an. However, most existing applications still implement a single last read feature, allowing users to save only one reading position and lacking a note feature for each saved reading position. This limitation creates difficulties for users who engage in multiple reading activities, such as tilawah (Qur'an recitation), hifz (memorization), and study sessions. This study aims to design and develop a Flutter-based mobile Qur'an application featuring Multi Last Read and Notes to improve the flexibility of managing Qur'an reading activities. The research employed the Research and Development (R&D) method, while the system was developed using the Software Development Life Cycle (SDLC) with the Waterfall model. System testing was conducted using Black Box Testing, White Box Testing, and User Acceptance Testing (UAT) involving 30 respondents selected through a purposive sampling technique. The results indicate that the application successfully implements the Multi Last Read feature, enabling users to save multiple reading positions based on different categories and add notes to each saved reading position. The Black Box Testing results demonstrate that all application functions operate according to the specified functional requirements, while the White Box Testing results confirm that the program logic satisfies the Cyclomatic Complexity and independent path analyses. Furthermore, the UAT results achieved a user acceptance rate of 97.79%, which falls into the Excellent category. Therefore, the developed application provides a more flexible, well-organized, and personalized Qur'an reading experience that meets users' needs.